Utilisation of animated video as a media for da'wah communication in the era of disruption - Nuryati, Wulan; Darmawan, Ferry; Zakiah, Kiki (Program Studi Ilmu Komunikasi, 2025)
This study examines the transformation of Islamic da'wah communication through animated media on Instagram, focusing on how visual aesthetics and narrative strategies influence the construction of religious meaning and audience engagement. Unlike previous research that mainly examined audience responses, this study integrates visual communication theory, symbolic interactionism, and the sociology of religion to analyze how animation redefines religious authority and identity in digital spaces. Using a qualitative case study, data were collected through in-depth interviews, observation, and content documentation from four purposively selected Instagram accounts. Thematic analysis was employed to identify patterns in narrative construction, symbolic representation, and audience interpretation. Findings reveal that animation functions not only as a tool for message delivery but also as an active medium of theological construction and identity formation for Gen Z Muslims. The study makes a theoretical contribution to the mediatization of religion and offers practical insights for digital da'wah strategies in contemporary contexts.